Factors that determine a university community’s satisfaction levels with public transit services - Arif Khan, Muhammad; Patel, Ronik Ketankumar; Pamidimukkala, Apurva; Kermanshachi, Sharareh; Rosenberger, Jay Michael; Hladik, Greg; Foss, Ann (Frontiers in Built Environment, 2023)
Universities and other educational institutions across the United States collaborate with service providers to afford their students, faculty, and staff transit services, such as dedicated buses, on-demand ridesharing, and public transportation. The university community relies on these services, especially in rural and low-density areas without fixed-route transit services. The literature on this topic has a wealth of detailed material about the travel and usage patterns of public transit systems, but it has little information about users’ satisfaction with the transit services provided by universities. This study focuses on filling this gap by using descriptive statistics and ordered logistic regression to determine how satisfied users are with university transit services and what factors are associated with their level of satisfaction. Four public transit services available to the University of Texas at Arlington community served as our case studies, and the results revealed that most users are satisfied with the services overall. Riders were highly satisfied with service attributes like ease of boarding, cleanliness, customer service, and vehicle speed of the four services. On the other hand, they were least satisfied with service availability and wait times of these services. The findings from this study may be used to provide the UTA community with better mobility and accessibility options and to evaluate the levels of satisfaction with similar services offered to other university communities.